A majority of parents of children with peanut allergy fear using the epinephrine auto‐injector. Issue 12 (12th October 2013) - Chad, L.; Ben‐Shoshan, M.; Asai, Y.; Cherkaoui, S.; Alizadehfar, R.; St‐Pierre, Y.; Harada, L.; Allen, M.; Clarke, A.
Abstract Prompt epinephrine administration is crucial in managing anaphylaxis, but epinephrine auto‐injectors (EAIs) are underutilized by patients and their families. Children with peanut allergy were recruited from the Allergy Clinics at the Montreal Children's Hospital, food allergy advocacy organizations and organizations providing products to allergic individuals. Parents of children who had been prescribed an EAI were queried on whether they were fearful of using it and on factors that may contribute to fear. A majority of parents (672/1209 = 56%) expressed fear regarding the use of the EAI. Parents attributed the fear to hurting the child, using the EAI incorrectly or a bad outcome. Parents whose child had longer disease duration or a severe reaction and parents who were satisfied with the EAI training or found it easy to use were less likely to be afraid. Families may benefit from simulation training and more education on the recognition and management of anaphylaxis.